2012
DOI: 10.1177/1553350612458546
|View full text |Cite
|
Sign up to set email alerts
|

New Synthetic Prosthesis for Peripheral Nerve Injuries

Abstract: The results indicate that implantation of the nerve prosthesis allows for good and effective neural regeneration. This new and simple treatment option for peripheral nerve injuries can be performed in any hospital with surgical facilities as it does not involve the demanding microsurgical suture technique that can only be performed in specialized centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Larger animal models are ideal for simulating the long-distance nerve defects and regenerative phenomena that are observed in human PNI. Since these models can more reliably replicate some characteristics of human nerves, such as their structural composition, dimensions, diameter and regenerative process, there are already several published studies based on the use of dogs [16,17], cats [18], rabbits [19], non-human primates [20], pigs [13,21], mini-pigs [22], guinea-pigs [23], and sheep models [24].…”
Section: Introductionmentioning
confidence: 99%
“…Larger animal models are ideal for simulating the long-distance nerve defects and regenerative phenomena that are observed in human PNI. Since these models can more reliably replicate some characteristics of human nerves, such as their structural composition, dimensions, diameter and regenerative process, there are already several published studies based on the use of dogs [16,17], cats [18], rabbits [19], non-human primates [20], pigs [13,21], mini-pigs [22], guinea-pigs [23], and sheep models [24].…”
Section: Introductionmentioning
confidence: 99%
“…In the choice of materials for nerve guidance conduits, resorbability and biocompatibility, especially as reflected in non‐provocation of an inflammatory response, are of utmost importance and the gelatin we chose is optimal in this respect. No animal, either in the preliminary or the main study, showed any intolerance [15]. Our study leads to believe that the outer sheath of the conduit and the microtubules, both made of gelatin, provide a route for the budding and elongating axons to follow that mimics the natural structure of the neural pathway, with endoneural connective tissue covering the individual fascicles, and the individual nerve fibers being stabilized and protected from ingrowth of external connective tissue.…”
Section: Discussionmentioning
confidence: 79%
“…The conduit is composed of biocompatible absorbable gelatin [15]. The basic body is made of biocompatible absorbable gelatin with a length of 18 mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Larger animal models are ideal for simulating the long-distance nerve defects and regenerative phenomena that are observed in human PNI. Since these models can more reliably replicate some characteristics of human nerves, such as their structural composition, dimensions, diameter and regenerative process, there are already several published studies based on the use of dogs (29,30), cats (31), rabbits (32), non-human primates (33), pigs (26,34), mini-pigs (35), guinea-pigs (36), and sheep models (37).…”
Section: Introductionmentioning
confidence: 99%